Development of a topical formulation of a thiadiazole derivative - Yu. M. Kotsur; T. F. Chernykh; E. V. Flisyuk; I. A. Narkevich (Разработка и регистрация лекарственных средств)
Introduction. Development of broad-spectrum antibacterial medicines for treatment of bacterial and fungal infections of animal skin is an urgent task of pharmaceutical industry, medicine and agricultural industry. The most promising dosage form for the treatment of superficial infectious diseases is gel. The most important advantages are the absence of side effects associated with ingestion, as well as the formation of a protective film that prevents re-infection of the animal.Aim. To develop the composition of topical form in the form of gel on the basis of active pharmaceutical substance with a wide spectrum of antimicrobial action for therapy of infectious diseases of animal skin.Materials and methods. The object of the study was an original substance – thiadiazole derivative, obtained by the organic synthesis department of the Department of Organic Chemistry of the Federal State Budgetary Educational Institution of Higher Professional Education SPHFU of the Ministry of Health of Russia. Gel formers (sodium alginate and carbomer), propylene glycol, surfactants (surfactants), etc. were used in the work. The obtained thiadiazole gels were studied in terms of pH, appearance, thermostability, colloidal stability, film formation, in addition, the rheological properties of the gels were determined.Results and discussion. It was found that gels in which sodium alginate and carbomer acted simultaneously as gel formers had thixotropic properties providing the best stability of the structure. The gels in which glycerin was added formed an elastic film preventing damage and drying of the animal skin.Conclusion. As a result of this study, a topical formulation in the form of a gel containing a new thiadiazole derivative was developed for the treatment of infectious diseases of animal skin.